Mecanismos e padrões de distribuição da metacomunidade bentônica com diferentes modos de dispersão. - Petsch, Danielle Katharine (2014)
Complementary approaches, based in mechanisms and patterns, provide a promising perspective in understanding the factors structuring metacommunities. Furthermore, the use of a deconstructive approach separates species according to shared biological traits, making the results more evident. In this context, we investigated different mechanisms and distribution patterns that can be recognized, according to dispersal modes (active or passive) and hydrological periods (dry and flood) in the benthic invertebrates metacommunity of Upper Paraná River floodplain. Sampling was conducted in 18 lakes, in a month of flood and another of dry in 2011. In active dispersers, only the spatial component was significant in the flood, indicating a limited dispersion under these conditions, whereas in the dry, both environmental and spatial components were significant, suggesting a high dispersion. Regarding the distribution pattern of the group, in both hydrological periods, we recognized a Clementsian pattern. Especially in the dry season, when there is a greater environmental heterogeneity, winged insects could actively select the most appropriate lakes along an environmental gradient, and thus the distribution of these species could be associated with such gradient, creating a Clementsian pattern. Regarding passive dispersers, we found a random distribution, which in the flood season both environmental and spatial effects were significant, indicating a high dispersion. However, in the dry season only the spatial component was significant, suggesting a more limited dispersion. These invertebrates being passively dispersed may not be able to effectively track environmental variation among lakes. In addition, this group was influenced for the homogenization effect of aquatic environments during flood, which could facilitate the dispersion in this period. Therefore, such characteristics may favor the random establishment of these invertebrates that are passively dispersed between lakes. We highlight the complexity of biological communities, whose understanding may depend, as demonstrated, both deconstructive approaches (biological traits) as complementary (mechanisms and patterns), and how they change over time.